2020
DOI: 10.1093/neuros/nyaa535
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay Beyond Medical Readiness in a Neurosurgical Patient Population and Associated Healthcare Costs

Abstract: BACKGROUND Length of stay beyond medical readiness (LOS-BMR) leads to increased expenses and higher morbidity related to hospital-acquired conditions. OBJECTIVE To determine the proportion of admitted neurosurgical patients who have LOS-BMR and associated risk factors and costs. METHODS We performed a prospective, cohort analysis of all neurosurgical patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The significant finding of the RAI predicting eLOS in this patient population is imperative, as eLOS is associated with higher risk of hospital acquired conditions, postoperative complications, healthcare resource utilization, and delayed recovery. 23 Prior studies have shown the average length of stay for PA resection to be between 1 and 4 days, 24 with one study citing 4 days as eLOS, 25 therefore the results of our study further exemplify the significance of using frailty scoring within this patient population, specifically the RAI. The results of our study align with previous reports which show frailty is a significant predictor of worse outcomes in patients undergoing pituitary surgery.…”
Section: Discussionsupporting
confidence: 62%
“…The significant finding of the RAI predicting eLOS in this patient population is imperative, as eLOS is associated with higher risk of hospital acquired conditions, postoperative complications, healthcare resource utilization, and delayed recovery. 23 Prior studies have shown the average length of stay for PA resection to be between 1 and 4 days, 24 with one study citing 4 days as eLOS, 25 therefore the results of our study further exemplify the significance of using frailty scoring within this patient population, specifically the RAI. The results of our study align with previous reports which show frailty is a significant predictor of worse outcomes in patients undergoing pituitary surgery.…”
Section: Discussionsupporting
confidence: 62%
“…[ 9 ] However, controversy exists as evidence also shows that older patients are the patient cohort with the greatest likelihood of having an unnecessarily extended LOS when they were otherwise fit for discharge. [ 11 ] In addition, elderly patients are also the age-group with the greatest number of comorbidities, which significantly fluctuates on a patient-to-patient basis. Moreover, extended LOS is influenced by capacity at discharge locations and other socioeconomic factors, such as family circumstances and transportation availability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the importance of using resources in neurosurgery more economically has been made apparent during the ongoing COVID-19 pandemic. [5][6][7][8] The release of the study by Linzey et al 9 (published in Neurosurgery 88: E259-E264, March 2021), which explored causes of and solutions for excessive hospital stay in neurosurgery, comes at a time when this topic is more closely examined and widely discussed. According to the study findings, the most common causes of prolonged length of stay beyond medical readiness are inadequate rehabilitation and care facilities for postoperative patients, delays in insurance payments to healthcare providers, and family problems.…”
Section: To the Editormentioning
confidence: 99%